2022
DOI: 10.1111/jac.12625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of waterlogging stress on grain nutritional quality and pod yield of peanut (Arachis hypogaea L.)

Abstract: To investigate the effects of waterlogging stress on grain nutritional quality and pod yield, peanut plants were waterlogged for 3 and 6 days at 7, 14, 21, 28, 35, 42, 49, 56 and 63 days after gynophores touched the ground in 2019 and 2020. Results revealed that compared with the control treatment, the oil and starch content in grain increased, while crude protein and soluble sugar content decreased under waterlogging. Waterlogging stress increased the unsaturated fatty acids content but decreased the satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…The waterlogging-sensitive peanut variety Huayu 39 was used in all experiments. A previous report confirmed that 7 days after gynophores touched the ground (DAG) was a critical time window for the WATERLOGGING STRESS ON PEANUT KERNEL FILLING | 3199 response of kernel development to WS, and during this stage, WS caused a reduction of 10.69%−14.08% in peanut kernel weight (Zeng et al, 2022). However, the critical duration of the effect of WS on kernel filling at the critical time window has not yet been explored.…”
Section: Determining the Duration Of Ws That Affects Kernel Fillingmentioning
confidence: 97%
See 1 more Smart Citation
“…The waterlogging-sensitive peanut variety Huayu 39 was used in all experiments. A previous report confirmed that 7 days after gynophores touched the ground (DAG) was a critical time window for the WATERLOGGING STRESS ON PEANUT KERNEL FILLING | 3199 response of kernel development to WS, and during this stage, WS caused a reduction of 10.69%−14.08% in peanut kernel weight (Zeng et al, 2022). However, the critical duration of the effect of WS on kernel filling at the critical time window has not yet been explored.…”
Section: Determining the Duration Of Ws That Affects Kernel Fillingmentioning
confidence: 97%
“…The earlier and longer plants encounter WS during the pod-filling stage, the greater is the reduction in yield (Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Providing agricultural lands with more water than crops need causes excess water to accumulate in these lands, resulting in a rise in groundwater tables. Under these conditions, water replaces oxygen existing in the soil profile, which may hinder, or stop, the respiration of crops' roots and thus result in severe damage to most crops [4,5]. This is referred to as the "waterlogging" condition (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with alternate wetting and drying, constant-flooding irrigation decreases the PV, breakdown (BD), and setback (SB) viscosities, gelatinization enthalpy (Δ H gel ), and temperatures; however, the effect on starch granule size and amylopectin chain length distribution has different trends [ 21 ]. In peanuts, the contents of oil, unsaturated fatty acids, and starch in grain increased, while the contents of crude protein, soluble sugar, saturated fatty acids, and amino acids (essential, non-essential, and total) decreased under waterlogging [ 22 ]. Waxy maize is a special maize type with starch is composed of nearly pure amylopectin, which endows its high viscosity, low retrograde, and high stability than normal maize starch and widely used in some industries such as thickening agent, emulgator, adhesive, suspending agent, etc.…”
Section: Introductionmentioning
confidence: 99%